Potensi, Tingkat Pemanfaatan dan Keberlanjutan Ikan Sebelah (Psettodes spp.) di Perairan Selat Malaka, Kabupaten Serdang Bedagai, Sumatera Utara - Rina D’Rita Sibagariang; Miswar Budi Mulya; Desrita Desrita (AQUACOASTMARINE, 2014)
Sebelah fish (Psettodes spp.) is a demersal fish, which live in swallow waters and flat bottom. This fish can be caught using fish net, drift gill nets, and set gill nets. The purpose of this research was to determine the potential of sustainable with optimum effort, utilization rates and insistence, sustainability and management of fish resources in Malacca Strait. Research had been conducted in Mei – September 2014. The analysis of secondary data from 2009 – 2013 obtained from the Department of Marine and Fisheries Serdang Bedagai regency and Department of Marine and Fisheries North Sumatra province, and primary data obtained by performed questionnaires correspondent with the fishermen about the sustainability of Sebelah fish. The potential of sustainable prediction performed with Fox model. The result shown that MSY was 1.708.839 kg/year and optimum effort was 47.076 trips/year. Average utilization rate of 58,86% with an average insistence rate of 62,34%, while allowable catch 1.367.071 kg/year. The dimensional ecological, social, tecnological and ethical of Sebelah fish included in the sustainable category. The economic dimension included in the fairly continuous category. The management efforts was by selectivity of fishing gear, disallowance of fishing gear and control of fishing effort.Keywords: Psettodes spp., potential, utilization, sustainability, Malacca Strait.